The Standardized Prophylaxis and Risk Factors for Venous Thromboembolism in Patients of Respiratory Intensive Care Unit: A Retrospective Observational Study - Bin-Yan Fu MSc; Sheng-Xin Fan MSc; Jia-Zhou Liu MSc; Yu-Liang Liu MD; Xiao-Hui Wang MD; Hong Chen MD (Clinical and Applied Thrombosis/Hemostasis)
Background Critically ill patients in intensive care unit (ICU) are at high risk of venous thromboembolism (VTE). The standardized prophylaxis of VTE in these patients and the appropriate prevention protocols are not very clear. Method We enrolled 426 patients admitted to respiratory intensive care unit (RICU), all of them underwent Padua risk scoring and patients at high risk of VTE also underwent bleeding risk scoring. We compared the VTE prevention methods that followed the guidelines between two different bleeding risk groups and the VTE incidence of these two groups. We also analyzed the risk factors for VTE in RICU patients. Results In patients admitted to RICU, the rate of overall VTE prophylaxis was 71.3% (295/414), but the rate of standardized prophylaxis of VTE was only 32.6% (135/414). The standardized prophylaxis rate of VTE in high-risk bleeding patients was 40.3%, much higher than the 22.2% in low-risk bleeding patients ( P  < 0.001). There was also a significant difference in the incidence of VTE between the two groups (26.9%vs3.4%, P  < 0.001). 70 (16.9%) patients in RICU developed VTE, the multivariable logistic regression analysis showed that immobilization time, pulmonary encephalopathy, oral or inject corticosteroids, trauma or surgery within 3 months were independent risk factors of VTE in patients admitted to RICU, while pharmacological prophylaxis was a protective factor for VTE. The receiver operating characteristic (ROC) curve showed that the above composite indicators had a higher predictive value for RICU patients with VTE, with a ROC area under the curve (AUC) of 0.925 (95%CI 0.894–0.956, P  < 0.001). Conclusion Although the overall prophylaxis rate of VTE in patients admitted to RICU was high, the rate of standardized prevention was not ideal. Pharmacological prophylaxis may play an important role in preventing VTE in RICU patients and fruther studies are needed to explore the optimal thromboprophylaxis protocol for critically ill patients.